2007
DOI: 10.4049/jimmunol.178.12.7849
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Peptide Tolerance Therapy of Lupus Generates Plasmacytoid Dendritic Cells That Cause Expansion of Autoantigen-Specific Regulatory T Cells and Contraction of Inflammatory Th17 Cells

Abstract: Subnanomolar doses of an unaltered, naturally occurring nucleosomal histone peptide epitope, H471–94, when injected s.c. into lupus-prone mice, markedly prolong lifespan by generating CD4+25+ and CD8+ regulatory T cells (Treg) producing TGF-β. The induced Treg cells suppress nuclear autoantigen-specific Th and B cells and block renal inflammation. Splenic dendritic cells (DC) captured the s.c.-injected H471–94 peptide rapidly and expressed a tolerogenic phenotype. The DC of the tolerized animal, especially pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
212
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(224 citation statements)
references
References 53 publications
9
212
1
2
Order By: Relevance
“…The number of Th17 cells was found to be increased in (SWR ϫ NZB)F 1 lupus mice after stimulation with nucleosomes, and Th17 cells migrated to target organs in the setting of autoimmune disease (49). Here, we showed that the expression of IL-17 mRNA in Th17 AND NATURAL TREG CELLS IN SLEsplenocytes from MRL/lpr mice reached levels that were 468-fold higher than those in wild-type B6 mice.…”
Section: Discussionmentioning
confidence: 66%
“…The number of Th17 cells was found to be increased in (SWR ϫ NZB)F 1 lupus mice after stimulation with nucleosomes, and Th17 cells migrated to target organs in the setting of autoimmune disease (49). Here, we showed that the expression of IL-17 mRNA in Th17 AND NATURAL TREG CELLS IN SLEsplenocytes from MRL/lpr mice reached levels that were 468-fold higher than those in wild-type B6 mice.…”
Section: Discussionmentioning
confidence: 66%
“…14,15 Some dendritic cells (DCs), such as immature DCs (imDCs) and plasmacytoid DCs, exhibit regulatory but not stimulatory functions on CD4 1 T cells. [16][17][18][19] Therefore, these DCs, especially monocyte-derived imDCs, have been used to induce antigen-specific CD4 1 Tregs from naive precursors.…”
mentioning
confidence: 99%
“…Whole cell lysates were prepared from fractionated spleen cell subsets or whole splenocytes. CD4 T cells (macrophages plus DCs) were purified from splenocytes using a technique as previously described (21,22). Western blotting was then carried out (15,16), and blots were probed with primary goat anti-COX-2 antibody (sc-1745; Santa Cruz Biotechnology, Santa Cruz, CA) overnight at 4°C in 5% nonfat dry milk in TBST (60 mmoles/liter Tris base, 120 mmoles/liter NaCl, 0.5% Tween 20), and then incubated with a horseradish peroxidase-conjugated secondary antibody (sc-2020; Santa Cruz Biotechnology) in 5% dry milk in TBST for 1 hour at RT.…”
Section: Quantitation Of Autoantibodiesmentioning
confidence: 99%